O uso da contabilidade na gestão de empresas de pequeno e médio porte: uma análise em empresas de transporte público urbano por ônibus - Araujo, Daniel Tonsic de (2018)
This study has aimed at verify the applicability of accounting information in SME companies of public transportation sector as well attempts to understand the importance given by these companies owner-managers to the accounting statements. This qualitative research has applied semi structured interviews method. Even if there are a reasonable number of qualified SMEs firms only three companies volunteered to participate. Based on the results, it was possible to note that ownermanagers recognize the importance of the accounting information on the decision making, with more relevance to the strategic management and tax information. The respondents also pointed out great relevance for the information timeliness and, due to the predominance of outsourced offices, all the respondents claimed for closest contact with the company accountant helping to deal with daily setback related do financial and tax information